KEMAMPUAN KUALITAS AUDIT MEMODERASI PENGARUH FRAUD HEXAGON TERHADAP FRAUDULENT FINANCIAL STATEMENTS - Sugi Suhartono; Arshinta Chandra Sari (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
This study aims to determine the influence of the hexagon fraud factor, namely financial stability, nature of industry, total accrual total assets, CEO's Education, frequent number of CEO's picture, state owned enterprise on potential fraudulent financial statements with audit quality as a moderating variable. This study uses company objects in the consumer goods industry sector which are listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling technique in this study was a non-probability sampling technique using purposive sampling method, resulting in 164 samples. The results show that financial stability, nature of industry and total accrual total assets have a positive effect on the potential for fraudulent financial reporting. CEO's education, frequent number of CEO's picture, and state owned enterprise have no effect on the potential for fraudulent financial statements. The moderating variable of audit quality is proven to be able to weaken the positive effect of financial stability on the potential for fraudulent financial reporting. The moderating variable of audit quality is not able to weaken the positive influence of nature of industry and total accruals of total assets on potential fraudulent financial statements.